The effect of factors related to merchandising on retail sales - Feijó, Fabrício Rodrigues; Botelho, Delane (RAE - Revista de Administracao de Empresas, 2012)
The studies of Mehrabian and Russell (1974), (researchers in the field of environmental psychology), have been instrumental in spreading the idea that the environmental features at the point of sale cause emotional reactions that lead to behavior that is hard to explain from a cognitive standpoint. For this reason, merchandising implementation plays a key role, since its aim is to provide an appropriate store atmosphere and display products in a way that encourages buying activity. This paper investigates the effects of merchandising factors on retail sales.The study was carried out in two types of stores: experimental – where merchandising factors were employed, and control - where the design features of merchandising remained unchanged.The analysis of the results confirmed the income effect. . The increase in revenue can be an indicator that merchandising factors have an influence on the consumer´s store choice criteria and his/her behavior within a determined sales environment.